PENGEMBANGAN MEDIA PEMBELAJARAN PUZZLE BERBASIS ETNOMATEMATIKA MELAYU RIAU PADA MATERI PECAHAN SEDERHANA UNTUK SISWA SEKOLAH DASAR - Andella, Monica; Fendrik, Muhammad; Kartika Sari , Intan (STKIP Subang, 2026)
This study aims to develop a puzzle based learning media grounded in Riau Malay ethnomathematics on the topic of simple fractions that is valid and practical for third grade elementary school students. Ethnomathematics is integrated through the use of Bolu Kemojo, a traditional cake from Riau Malay culture, as a contextual representation in understanding fraction concepts. This research employed a Research and Development (R&D) method using the ADDIE model, which consists of five stages: analysis, design, development, implementation, and evaluation. The analysis stage was conducted to identify students needs and difficulties in understanding simple fractions. The design stage involved developing puzzle based learning media incorporating Riau Malay cultural elements along with supporting worksheets. The development stage produced a validated product assessed by material and media experts. The implementation stage was carried out through limited and field trials, while the evaluation stage was conducted formatively throughout the development process. The subjects of this study included material experts, media experts, a third grade teacher, and third grade students of SD Negeri 51 Pekanbaru. The research instruments consisted of validation sheets and response questionnaires from teachers and students. The results showed that the developed media achieved a validity score of 91.6% from material experts and 98.8% from media experts, both categorized as very valid. The practicality results indicated student responses of 98.8% in limited trials and 97.8% in field trials, as well as a teacher response of 98%, all categorized as very practical. Therefore, the developed learning media is feasible to use and can help students understand fraction concepts more concretely and contextually.